Intra-Cardiac Tumor and Thrombi Classification in ECG based on Kernel Collaborative Representation - Raj , R.S. Sidharth; Karthik, B. (International Journal of Psychosocial Rehabilitation, 2018)
Identification of intracardiac masses in echocardiograms is one important task in cardiac disease diagnosis. To im-prove diagnosis accuracy, a novel fully automatic classification method based on the sparse representation is proposed to distinguish intracardiac tumor and thrombi in echocardiography. First, a region of interest is cropped to define the mass area. Then, a unique globally denoising method is employed to remove the speckle and preserve the anatomical structure. Subsequently, the contour of the mass and its connected atrial wall are described by the K-singular value decomposition and a modified active contour model. Finally, the motion, the boundary as well as the texture features are processed by a kernel collaborative representation classifier to distinguish two masses. Ninety-seven clinical echocardiogram sequences are collected to assess the effectiveness.